The Christmas letter [videorecording (DVD)] - Cunningham, Michael (Screenwriter); Benfield, Angus; Chase, Chevy; Quaid, Randy, 1950-; Doyle-Murray, Brian (BMG Global, 2024)
Every year, an unemployed writer reads his wealthy friend's over-the-top Christmas letter, feeling like a loser. But this year is going to be different as he is determined to change his luck by gambling everything to feel like a winner.